Konstelasi Badan Usaha Milik Desa Sektor Pariwisata di Kabupaten Kerinci - Alda Srilupita; Rozalinda; Ahmad Wira (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2024)
Village development through BUMDES is sometimes not fully managed well, this is caused by a lack of understanding and also a lack of knowledge regarding BUMDES management both from village institutions and the community itself. The purpose of this article is to find out the role of BUMDES in empowering the community and also improving community welfare. In this research, descriptive qualitative research methods were used through case studies of BUMDES institutions and also the community of Pendung Talang Genting Village. The data collection technique used was interviews with the Head of BUMDES and the community. The data analysis technique used uses data reduction, data presentation and also drawing conclusions. The findings in this research show that in 2022 BUMDES Pendung Talang Genting Village will become one of the best villages in Kerinci Regency and represent Jambi province in the village award with the ADWI category ranking 5th out of 50 tourist villages throughout Indonesia under the auspices of the Minister of Tourism and Economy Creative. BUMDES Taman Pertiwi provides employment opportunities for youth or youth organizations in the form of human resource development. BUMDes Taman Pertiwi Pendung Talang Genting Village has had a good impact on the community, such as opening up employment opportunities, providing educational assistance to underprivileged children and also providing basic necessities to the community every month of fasting. The results of this research strengthen the results of previous research which confirms the important role of BUMDes in community economic development.